ESTIMATION OF RADIATION DOSE AND ORGANS AT RISK (OAR) ON ABDOMINAL CT-SCAN USING SIZE-SPECIFIC DOSE ESTIMATES (SSDE) METHOD - Sari, Kamelin Diah; Sutapa, Gusti Ngurah; Kasmawan, I Gde Antha; Sandi, I Nengah; Artawan, I Nengah; Trisnawati, Ni Luh Putu; Widiana, I Komang (Indonesian Physical Review, 2023)
A study has been carried out on the estimation of radiation dose and Organs at Risk (OAR) on abdominal CT-Scan examination using the SSDE method. The data used in this study were secondary data from medical records such as CTDIVol, DLP, and abdominal images of patients. This study aims to determine the size of SSDE, DE, and DEOAR and to determine whether DE is still within tolerance limits to ensure the feasibility of using CT-Scans in these installations. The SSDE value is obtained by multiplying the converted def value (f) and the CTDIVol, while the DE value is obtained by multiplying the DLP value and the conversion factor (k), finally, the DEOAR value is obtained by multiplying the CTDIVol and the organ/tissue weight factor. The results showed that the patient's average SSDE score was 12.04 ± 1.06 mGy, with a male SSDE value of 12.55 ± 1.30 mGy and a female SSDE value of 12.38 ± 2.47. While the average patient DEOAR value obtained was 7.57 ± 0.72 mGy and the patient's average DEOAR value for skin and bone surface was 0.09 ± 0.01 and red bone marrow and large intestine was 1.06 ±0.13. The DE value of this study is still below the tolerance value set by BAPETEN, which is less than 17.46 mGy.